PEMBELAJARAN MENULIS PUISI MENGGUNAKAN METODE EXPERIENTIAL LEARNING BERBANTUAN MEDIA LAGU PADA PESERTA DIDIK KELAS X SMK PASUNDAN 1 BANDUNG: Penelitian - Kamiliya Khaerunisa; Dindin M.Z.M.; Setiawan (STKIP Subang, 2023)
ABSTRACT This research is motivated by the low writing skills of students, which is caused by the lack of variation in teaching methods used by educators. The use of varied and creative teaching methods can make students more active and motivated during learning activities. One creative method that can be used is the experiential learning method. The objectives of this research are to test the author's ability to plan, implement, and evaluate poetry writing lessons using the experiential learning method for students of class X at Pasundan 1 Vocational High School in Bandung; to test the ability of students in class X at Pasundan 1 Vocational High School in writing poetry according to its structural elements; to determine the differences in poetry writing between the experimental class using the experiential learning method and the control class using the discussion method; and to test the effectiveness of the experiential learning method in poetry writing lessons for students of class X at Pasundan 1 Vocational High School in Bandung. In its implementation, the author used a quantitative method. The data obtained consisted of pretest and posttest scores of students from both the experimental and control classes. The findings of this research are as follows: 1) The author was able to plan, implement, and evaluate poetry writing lessons using the experiential learning method, with an average planning score of 3.7 and an average implementation score of 4, which falls into the category of very good. 2) The students' ability in writing poetry showed improvement. In the experimental class, the average pretest score of 57 increased to a posttest score of 77. In the control class, there was an improvement with an average pretest score of 36 increasing to a posttest score of 55. 3) There is a significant difference between the experimental class and the control class. 4) The experiential learning method is effective in teaching poetry writing. This is evidenced by the Mann-Whitney test results, which revealed a sig. value of 0.000 < 0.05. Based on the above explanation, the experiential learning method can be considered as an effective alternative teaching method for writing poetry. Keywords: teaching method, experiential learning, writing, poetry.